2014
DOI: 10.3906/vet-1305-10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spirulina in arsenic poisoning in the Black Bengal goat

Abstract: the uplift of the CAP margins started (Yildirim et al. 2011;Cosentino et al. 2012;Schildgen et al. 2012). Here we describe the type section of the Tuğlu Formation, a sequence exceptionally rich in fossils. The section has been sampled for micropalaeontological (ostracods, foraminifera, pollen, Characeae), palaeontological (molluscs, small mammals, fish remains), environmental magnetism, and stable carbon and oxygen isotope analyses (on ostracods and bulk sediment samples) as well as strontium isotope analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 84 publications
(82 reference statements)
5
7
0
Order By: Relevance
“…Spirulina reduced As level significantly from the tissues compared to only arsenic treated rats which was in agree with finding of Fariduddin et al (2001), who stated that spirulina was effective in lowering arsenic level from the arsenic loaded tissues in rats and Ghosh et al (2014), who stated that spirulina was effective in lowering of arsenic level from blood of induced arsenicosis in goats. Vitamin E reduced As level significantly from the tissues compared to only arsenic treated rats that agreed with the findings of Islam et al (2005), who stated that supplementation of vitamin E, iron and zinc reduces the arsenic concentration in tissues like liver, kidney, spleen, heart, intestine, stomach, muscle and dermis of rats as well as lower the tissue damage caused by arsenic.…”
Section: Discussionsupporting
confidence: 82%
“…Spirulina reduced As level significantly from the tissues compared to only arsenic treated rats which was in agree with finding of Fariduddin et al (2001), who stated that spirulina was effective in lowering arsenic level from the arsenic loaded tissues in rats and Ghosh et al (2014), who stated that spirulina was effective in lowering of arsenic level from blood of induced arsenicosis in goats. Vitamin E reduced As level significantly from the tissues compared to only arsenic treated rats that agreed with the findings of Islam et al (2005), who stated that supplementation of vitamin E, iron and zinc reduces the arsenic concentration in tissues like liver, kidney, spleen, heart, intestine, stomach, muscle and dermis of rats as well as lower the tissue damage caused by arsenic.…”
Section: Discussionsupporting
confidence: 82%
“…In agreement with previous studies regarding arsenic-induced nephrotoxicity in rats [12,26], mice [25] and goats [24], sections of kidney from arsenate treated mice in the current study showed glomerulonephritis, proximal tubular necrosis, epithelial damage and loss of nuclei, interstitial hemorrhages and mononuclear cell infiltration, as well as hyaline casts within the medullary tubules. In accordance with previous studies on arsenic-induced nephrotoxicity in rats treated with ascorbic acid [12], in mice treated with Vitamin C and E [25] and in goats supplemented with spirulina [24], significant reno-protective effects were observed.…”
Section: Histopathologysupporting
confidence: 93%
“…In agreement with previous studies regarding arsenic-induced hepatotoxicity [12,24,26], liver sections from arsenate treated mice showed moderate to marked venous congestion, sinusoidal dilatation, multiple foci of mononuclear cell infiltration and parenchymal disorganization.…”
Section: Histopathologysupporting
confidence: 92%
See 1 more Smart Citation
“…Vitamin C, as well as any other water soluble antioxidants, scavenge ROS and play an important role in the regulation of intracellular redox state [7]. Several researchers investigated the histopathological effects of arsenicals on the liver and kidney of rats, mice and goats [12,[23][24][25][26].…”
mentioning
confidence: 99%